Evaluasi Implementasi Kebijakan Perlindungan Keluarga Miskin di Kota Ambon - Meilani Djabumir, Gracia; Normawaty Normawaty; Pattimukay, Hengky Virgo Richardo; Patty, Julia Theresia (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
This study was conducted to enrich the literature and scientific understanding of the phenomenon of poverty, especially in urban contexts such as Ambon City. The method applied in this study is Qualitative with in-depth interview techniques. Based on the results of the research that has been done, it can be concluded that the Evaluation of Poor Family Protection Policy in Ambon City. shows that although the poor family protection policy in Ambon City provides benefits, there are obstacles in accessibility, coordination between agencies, and budget limitations that hinder program optimization. In addition, dependence on assistance and lack of community participation in policy planning are factors that inhibit its effectiveness. This study suggests improving the reporting and evaluation system, increasing coordination between agencies, and empowering the community to support the sustainability off the program.